Proceso de intervención aplicado a un paciente adulto mayor con trastorno depresivo en salud mental - Moyano Vera, Ligia Vanessa (2021)
This case study was developed in the decentralized Autonomous Government of the Alfredo Baquerizo Moreno canton with the main objective of determining the proper intervention in an elderly patient with depressive disorder. Some of the symptoms that depressive disorder generates are: sadness, insomnia, depressed mood, anhedonia, loss of appetite and weight, for which use the Beck test to verify the level of severity, among other techniques, with this He was able to obtain specific information from the patient and adequate treatment. Through this investigation, it was possible to show that there is indeed an increase in the levels of depression and its relationship in their environment.